Periphrases and Idiolects: Some Strategies In Replying to a Dialect Atlas Questionnaire - Babitch, Rose Mary; Péronnet, Louise; Cichocki, Wladyslaw (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2001)
Among the replies to the questions in the Atlas linguistique du vocabulaire maritime acadien is a small set of items which were constructed on the spot by the fishers-subjects and which form a separate category referred to as periphrases. Quantitative analyses reveal several associations among the question types, the semantic themes in the Atlas and the morphosyntactic structures which characterize these periphrases. The spatial distribution of these items shows considerable intersubject variation with only a small degree of geographic regularity. These findings suggest that the periphrases are idiolectal and that strategies used to produce them are shared across the geographic regions covered in the Atlas.